SELF REGULATED LEARNING DALAM BELAJAR AL-QUR’AN PADA REMAJA DI SIDOMULYO TUMBANG TAHAI PALANGKA RAYA - Salsabila Asyifana DLT; Hamidah Hamidah; Surawan Surawan (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2022)
The aim of this study was to descript Self Regulated Learning (SRL) of teenagers in Sidomulyo, Tumbang Tahai Village, Palangka Raya in learning the Qur'an independently. This research is based on phenomena that occur in the field, researchers see that some teenagers in Sidomulyo pay less attention to their intellectual responsibilities, especially in learning the Qur'an. This study uses a qualitative approach with data collection techniques using observations and interviews. The data were analyzed to obtain the findings of the research. The subjects in this study were teenagers in Sidomulyo who were enthusiastic in learning the Qur'an. The results of this study found that the majority of adolescents in Sidomulyo had low self-regulated learning (SRL), but there were some adolescents who had high SRL. Self-Regulated Learning (SRL) in adolescents in learning the Qur'an independently is influenced by several supporting and inhibiting factors. The supporting factors are; 1) self-efficacy, 2) self-motivation, and 3) family social support. While the inhibiting factors that affect Self Regulated Learning (SRL) in learning the Al-Qur'an independently in adolescents in Sidomulyo are; 1) lack of family support, 2) Busy work.